Propranolol is an effective treatment for airway haemangiomas: a critical analysis and meta-analysis of published interventional studies - VLASTARAKOS, P.V. (Pacini Editore SpA, 2012)
Haemangiomas represent the most common benign tumours in infancy, affecting 1-2% of newborns. The present meta-analysis aimed to critically review the current evidence on the efficacy of propranolol in the management of airway haemangiomas, and explore potential adverse events and treatment failures. A literature review was performed in Medline and other available database sources, along with critical analysis of pooled data. Seventeen studies were included in the analysis. No study represented Level I evidence. The total number of treated patients was 61; 14 patients received propranolol as single-treatment. The comparative effectiveness of propranolol vs. systemic steroids was documented in 35 children, and showed superior outcome in the vast majority (94%, p < 0.001). The mean obstruction before propranolol administration was 72%, and after intervention was 20% (p < 0.001). The mean referral-age for children with airway haemangiomas was 2.4 months, the mean starting-age of propranolol treatment was 5.1 months and the mean follow-up period was 8.4 months. Four children failed to respond (6.5%), and in seven the haemangioma relapsed after discontinuation of treatment (11.5%). The results of the present study suggest that propranolol can be recommended for the treatment of airway haemangiomas, as it was found to be effective and outperformed the previously-considered gold standard treatment methods, with fewer side-effects. Immediate treatment with propranolol should be initiated once a diagnosis of symptomatic airway haemangioma is confirmed, and cardiovascular assessment has been performed. Children should remain on propranolol until the haemangioma enters the phase of involution. Active parental monitoring is essential to ensure treatment safety.